Synthesis and Characterization of Nafion-SiO2 Composite Membranes as an Electrolyte for Medium Temperature and Low Relative Humidity - Mahreni Mahreni; Eniya Listiani Dewi; Tjukup Marnoto; Harso Pawignyo; Purwo Subagyo; Endang Sulistyowati (Chemical Engineering Diponegoro University, 2011)
The weakness of the Nafion membrane as electrolyte of PEMFC associated with physical properties that is easy to shrink at temperatures above 80°C due to dehydration. Shrinkage will decrease the conductivity and membrane damage. Nafion-SiO2 composite membranes can improve membrane stability. The role of SiO2 in the Nafion clusters is as water absorbent cause the membrane remains wet at high temperatures and low humidity and conductivity remains high. The results showed the content of 2.8 wt% of SiO2 in the Nafion membrane, the conductivity of composite membrane is higher than the pure Nafion membrane that are 0.127 S cm-1 in dry conditions and 0.778 S cm-1 in wet conditions at room temperature. Compared with the pure Nafion membrane conductivity are 0.0661 S cm-1 and 0.448 S cm-1 respectively in dry and wet conditions.